Penyelesaian Pembagian Warisan Di Kecamatan Simpang Ulim Dalam Perspektif Hukum Islam dan Hukum Adat - Muhammad Nasir, Khalidah (Hukum Keluarga Islam IAIN LANGSA, 2021)
In Acehnese society, the implementation of inheritance law is influenced by customary law living in the community, the heirs are in accordance with what has been stipulated in faraid law, but in the distribution of wealth sometimes it does not follow faraid law, but according to mutual agreement. Determination of inheritance in the Acehnese community in Simpang Ulim District, whose majority Muslim community, in terms of handling inheritance more depends on the heirs, this method is called the familial way and can run well without conflict, for example, the parties agree to divide the number of the expert's assets. the inheritance for boys is equal to that given to girls. This research is a field study with a qualitative approach. The primary sources in this study were informants from the Simpang Ulim Community whose data were taken by random sampling. The results of the study concluded two things; First, the mechanism for implementing the distribution of the inheritance of the Acehnese people in Simpang Ulim District is carried out in two ways, firstly by purely Islamic law, and by means of kinship (custom). The reason for the implementation of the family system is because the majority of people do not understand the law of inheritance in totality in Islam. Second, the application of Islamic inheritance law to the implementation of inheritance law in the Acehnese people in Simpang Ulim District is complementary and side by side with customary law. On this occasion, the heirs will ask for guidance from religious leaders by kinship consensus.